Portugal : Fifth Post Program Monitoring Discussions-Press Release; Staff Report; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report ;, 2017)
The Fifth Post-Program Monitoring Discussions with Portugal highlight a welcome upturn in growth in the second half of 2016 after a sluggish first half, boosted by stronger exports and a further decline in unemployment to precrisis levels. These developments point to an improved near-term outlook, but medium-term growth could be put on a more sustainable footing by reducing structural bottlenecks and high levels of corporate debt. The revised 2016 fiscal target appears likely to have been met, but prospective public outlays for banking sector recapitalization continue to weigh on public debt trends.